METODE PENDIDIKAN BERBASIS KETELADANAN (USWAH HASANAH) GURU SEBAGAI STRATEGI MANAJEMEN SDM PENDIDIK DALAM PENDIDIKAN ISLAM - Rahmawati, Rahmawati; Uswatun , Sri; Naufal Athallah, M.; Alimron, Alimron; Mukmin, Mukmin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Exemplary-based education (uswah hasanah) is a fundamental approach in Islamic education that plays a crucial role in shaping students’ character, moral integrity, and academic culture. This article aims to analyze the concept of teachers’ uswah hasanah from the perspectives of the Qur’an and Hadith and to examine its relevance as a human resource management (HRM) strategy for educators in Islamic educational institutions. This study employs a qualitative approach using library research. Primary data are derived from the Qur’an and the Hadith of the Prophet Muhammad (peace be upon him), while secondary data include Qur’anic exegesis, Islamic education literature, and relevant previous studies. Data were analyzed using content analysis and descriptive-analytical methods to explore the normative and practical dimensions of exemplary leadership in education. The findings indicate that uswah hasanah has a strong theological foundation, particularly in Qur’an Surah Al-Ahzab (33:21), and functions as a transformative method of value internalization through real-life examples rather than verbal instruction alone. From a tafsir tarbawi perspective, teachers’ exemplary conduct can be positioned as a strategic framework for managing educational human resources, encompassing integrity-based recruitment, continuous professional development, ethical performance evaluation, and the establishment of a compassionate organizational culture. Therefore, uswah hasanah serves not only as a character education method but also as a strategic model for educator management in Islamic education (teacher).